2014
DOI: 10.1002/hbm.22653
|View full text |Cite
|
Sign up to set email alerts
|

Degraded EEG decoding of wrist movements in absence of kinaesthetic feedback

Abstract: A major assumption of brain–machine interface research is that patients with disconnected neural pathways can still volitionally recall precise motor commands that could be decoded for naturalistic prosthetic control. However, the disconnected condition of these patients also blocks kinaesthetic feedback from the periphery, which has been shown to regulate centrally generated output responsible for accurate motor control. Here, we tested how well motor commands are generated in the absence of kinaesthetic feed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…Therefore, it is unlikely that neural activity of other cortical areas like neck region affects decoding procedure. In addition, unlike EEG based studies that have proved the effect of somatosensory feedbacks on decoding 24 , using the intracortical techniques with higher spatial resolution can diminish the effect of sensory inputs (muscle spindles or Golgi tendons) in the force decoding. However, this impact cannot be completely ignored due to the projection of proprioceptive information to the motor cortex 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is unlikely that neural activity of other cortical areas like neck region affects decoding procedure. In addition, unlike EEG based studies that have proved the effect of somatosensory feedbacks on decoding 24 , using the intracortical techniques with higher spatial resolution can diminish the effect of sensory inputs (muscle spindles or Golgi tendons) in the force decoding. However, this impact cannot be completely ignored due to the projection of proprioceptive information to the motor cortex 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, fMRI studies have shown activation of a distributed frontoparietal occipital network during motor planning, imagery, and execution [35,36,51]. EEG source analysis has shown that physical suppression of the kinaesthetic reafference reduces the source activity at pre and postcentral sites and that the same occurs during imagined movements in which the sensory reafference is absent [52]. In highs, the lack of sensory information could be replaced by its mental image owing to their stronger functional equivalence between imagery and action [27,29].…”
Section: Hypnotizability and Motor Imagerymentioning
confidence: 99%
“…As the muscle contracts, the sensory neurons reporting its status reduce their firing rates. Normally, response neurons that directly generate movement require proprioceptive sensory inputs to be able to do so [Galán et al, 2015]. Without proprioceptive inputs, the abrain can learn to activate motor neurons adaptively via a different modality (e.g., vision), but this requires extensive training [Cole and Paillard, 1995].…”
Section: The Innate Response Networkmentioning
confidence: 99%